THE ART OF STRUCTURED MUET SPEAKING: BUILDING STRUCTURED SPEECHES WITH SEQUENTIAL MOVE ANALYSIS FRAMEWORK (SMAF) - Nasir, Noormaizatul Akmar Muhamad; Yaacob, Nurul Husna; Razaki, Marina Muhammad; Arifin, Raihan Mohd; Ramanan, Banu (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The Sequential Move Analysis Framework (SMAF), derived from sequential move analysis, enhances language learners’ speaking skills by providing structured guidance on speech organization and strategy development. This approach helps learners understand the functional roles of different speech acts within a speaking presentation, promoting more effective and coherent communication. By incorporating sequential moves, learners are guided through a structured speaking process that fosters confidence and clarity. The framework is highly adaptable to various presentation themes, offering targeted practice aligned with specific language test objectives, such as the Malaysian University English Test (MUET). SMAF integrates individual presentation practices to serve as an immediate reference template for learners during task performance. The framework was tested in a simulated MUET speaking domain with English as a second language (ESL) learners. Results showed a significant improvement of 55.26% in speaking test scores, with a pre-test mean score of 17.6 and a post-test mean score of 27.325. The strong correlation (r=0.975) between pre-test and post-test scores suggests that integrating SMAF leads to enhanced performance in MUET speaking tasks. This framework provides a practical tool for MUET instructors, aiding students in structuring their responses more effectively and achieving better results in their speaking test.